Essentials of Good Governance in a Multilingual, Multiethnic and Multi-Religious Society: Developing an Effective Model for Nigeria - Akinola, Omoniyi Bukola (Legal Practice Discourse, 2021)
Good governance is the pillar upon which any good society stands and thrives. The aim of this paper is to examine the concept of good governance, the extent of its application in Nigeria and the need to develop an effective model for Nigeria considering its multilingual, multiethnic and multi-religious composition. The paper adopts the doctrinal approach in this research by examining current literature in this topic and making further recommendations for research while finding solutions in tolerance and adherence to the spirit and letters of a Constitution which is generally acceptable to all Nigerians both home and in diaspora
Keywords: Good Governance; Cultural differences